Pelatihan Membatik Gesek Godong “Memulai Usaha Dari Rumah” - Fellysia Tri R; Rahmawati Rahmawati; M. Fadjar Buwono; Salma Salsabila; Aulia Widhya P (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This Community Service focuses on training on how to make godong swipe batik which was developed by Small and Medium Enterprises (UKM) located at Pasar Johar Selatan, 3rd floor, Semarang City. This service aims to provide an understanding of the Godong swipe batik business to the community. The proposed solution is that this Godong friction batik training will help people who want to open a business with fast workmanship and is suitable for anyone. It is hoped that this training can motivate people to try opening a business. The results of this service include journal publications, training modules, documentation, press releases, final reports, increasing participants' knowledge and insight in making godong gesek batik. It is hoped that this service can help make a positive contribution to the sustainability of SMEs.